Grammatical and Syntatic Errors in L2 English Writing: The Impact of Language Inteference - AL Farisi, Muhammad Rafi; Malihah , Noor (Journal of Language and Literature Studies, 2024)
This research examines grammatical and syntactic errors in second language (L2) writing, with a focus on the role of mother tongue interference and developmental processes in second language acquisition. In L2 writing, errors are viewed not merely as mistakes to be corrected, but as reflections of the learner’s interlanguage—a transitional linguistic system that represents the learner’s current level of grammatical and syntactic understanding. Using a descriptive qualitative approach, this study relies on a literature review to analyze data from various experts in the field of second language acquisition. The common challenges identified include grammatical interference in the use of articles, prepositions, word order, and subject-descriptor agreement, along with syntactic errors such as inappropriate pronoun use and incorrect word order. The research distinguishes between errors caused by first language (L1) interference and those resulting from developmental processes in L2 learning, offering valuable insights into the learners’ evolving interlanguage systems. The study highlights the importance of targeted pedagogical interventions, such as comparative syntax lessons, focused feedback, and practical exercises, to address these errors and improve L2 writing proficiency. Ultimately, this research contributes to a deeper understanding of how L2 learners develop grammar and syntax skills, providing guidance for more effective teaching practices in language instruction.